Investigating the Analgesic Effects of the Chenopodium Botrys L. Hydroalcoholic Extract Using Behavioral Tests on Mice - Mohebbati, Reza; Beheshti, Farimah; Kakhki, Samaneh; Taghavizadeh Yazdi, Mohammad Ehsan (Iranian Journal of Pharmaceutical Sciences, 2023)
Regarding the unpleasant pain sensation and the public’s desire to use traditional herbs, the present study aimed to assess the analgesic and anti-inflammatory effect of Chenopodium botrys L. The present research was divided into two main sections to assess the analgesic and anti-inflammatory effect of Chenopodium botrys L. in male mice. To investigate the analgesic effect of Chenopodium botrys L., thirty-six male mice were randomly classified into six groups vehicle (receiving normal saline), experimental groups received morphine (a well-known opioid, 1 mg/kg), hydroalcoholic extracts of Chenopodium botrys L. (30, 100, and 300 mg/kg), and naloxone (opioid receptor antagonist) with the highest dose of Chenopodium botrys L. concurrently for one week. Thirty mice were divided into five groups to receive normal saline, various doses of extract (30, 100, and 300 mg/kg), and dexamethasone (a well-known anti-inflammatory drug, 10 mg/kg) to assess the anti-inflammatory effect of Chenopodium botrys L. In both sections, after the last doses of the treatment, the animals got ready for behavioral study related to pain. Overall, the highest doses of Chenopodium botrys L. demonstrated much better results than other doses, which were comparable to opioids and dexamethasone, a well-known analgesic and anti-inflammatory medicines, respectively. Regarding present findings, the Chenopodium botrys L. plant can be a new candidate as an analgesic agent, which needs more investigation in the search and pharmaceutical development.